EFFECTIVENESS COMBINATION OF HEGU AND TAIXI POINT ACUPRESSURE WITH RED GINGER HYDROTHERAPY ON PAIN SCALE IN GOUT ARTHRITIS CLIENTS - Nadia Sari; Lisa Rahmi (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
Arthritis gout is a disease caused by a purine metabolism disorder characterized by hyperuricemia and recurrent attacks of acute synovitis causing severe pain in the joint area. One of the treatments for gout arthritis with non-pharmacological therapy is acupressure and warm red ginger hydrotherapy which is able to relax muscles, increase blood circulation, and can stimulate the effector system causing peripheral vasodilation so that blood flow to tissues is smooth, especially tissues that are inflamed so that it can reduce inflammation joint pain. This study aims to determine the effectiveness of the combination of acupressure on the hegu and taixi with red ginger hydrotherapy as a complementary nursing intervention in reducing pain in gouty arthritis sufferers. Quantitative research with true experiment approach pre and post-test control group design involving 30 respondents divided into intervention group (n=10) given acupressure and red ginger hydrotherapy, while control group 1 (n=10) was given acupressure and control group 2 (n =10) was given red ginger hydrotherapy. The sampling technique used probability sampling with simple random sampling based on inclusion and exclusion criteria. Then the research results were analyzed using parametric tests, namely Paired t test, ANOVA test and Post Hoc Bonferroni test. The ANOVA test showed a significant value of p = 0.000 (<0.05), while the Post Hoc Bonferroni test showed that between the intervention group and control 1 there was a difference with a significant value of p = 0.001, between the intervention group and control 2 there was a difference in the value significant p=0.005 and between control group 1 and control 2 there was no difference with a significant value of p=1,000. There was a difference between the intervention group, control group 1 and control group 2, which means that the administration of acupressure at the hegu and taixi with red ginger hydrotherapy was more effective in reducing pain in gouty arthritis patients than acupressure and red ginger hydrotherapy alone.